von Willebrand factor mutation enhancing interaction with platelets in patients with normal multimeric structure. - Holmberg, L (1993)
Variant von Willebrand disease designated as type I New York or type Malmö is characterized by enhanced ristocetin-induced platelet agglutination with normal von Willebrand factor multimeric distribution in plasma. We have studied four such patients belonging to three unrelated families and found in all of them a unique cytosine-to-thymine transition changing the codon for Pro503 (CCG) to Leu (CTG). In three patients the mutant allele also had a silent mutation in the codon for Ser500 (TCG-->TCA). Both nucleotide changes are present in the von Willebrand factor pseudogene; however, the characterization of distinctive markers where the gene and pseudogene differ, as well as the examination of amplified cDNA derived from platelet mRNA, confirmed that the abnormality occurs in the von Willebrand factor gene of the patients. Moreover, recombinant expression of the isolated glycoprotein Ib-binding domain of von Willebrand factor provided direct evidence that the Pro503-->Leu mutation is responsible for enhanced platelet reactivity to lower ristocetin concentrations. These results define a new structural element affecting the affinity of von Willebrand factor for glycoprotein Ib and establish the molecular basis of a variant form of von Willebrand disease.